Sustained response to guselkumab regardless of baseline characteristics in patients with active psoriatic arthritis and inadequate response to TNF inhibitors: results from the phase 3b COSMOS clinical trial - Iain B McInnes; Laura C Coates; Philipp Sewerin; Frédéric Lavie; Mohamed Sharaf; Miriam Zimmermann; Michela Efficace (RMD Open, 2024)
Objectives To prospectively evaluate the effect of guselkumab through 48 weeks across various clinical outcomes in subgroups of patients with psoriatic arthritis (PsA) and inadequate response to tumour necrosis factor inhibitors (TNFi-IR) from the phase 3b COSMOS trial. Subgroups were defined by baseline demographics, disease characteristics and prior/ongoing therapies.Methods Patients with active PsA (tender joint count (TJC) and swollen joint count (SJC) both ≥3) and TNFi-IR were randomised 2:1 to receive guselkumab 100 mg at week 0, week 4, then every 8 weeks through week 44 or to placebo with cross-over to guselkumab 100 mg at week 16 (early escape) or week 24 (planned). Guselkumab effect on joints (American College of Rheumatology (ACR) 20/50/70, enthesitis, dactylitis), skin (Psoriasis Area and Severity Index 90/100, Investigator’s Global Assessment 0/1), patient-reported outcomes (PROs) (Functional Assessment of Chronic Illness Therapy–Fatigue, Health Assessment Questionnaire–Disability Index) and composite outcome measures (PsA Disease Activity Score low disease activity, minimal disease activity) were evaluated by baseline patient age, sex, body mass index, SJC, TJC, PsA duration, %body surface area, C reactive protein, pain Visual Analogue Scale, number of prior TNFi and discontinuation reason, and conventional synthetic disease-modifying antirheumatic drug status. Results are descriptive only.Results Baseline characteristics were similar between guselkumab (n=189) and placebo (n=96) groups. The benefit of guselkumab over placebo in achieving ACR 20 (primary endpoint; 50% vs 28%) and ACR 50 (23% vs 8%) response at week 24 was observed within all subgroups. Furthermore, response rates in the guselkumab group increased between week 24 and week 48 within almost all subgroups. Similar response patterns at week 24 and through week 48 were observed across various clinical outcomes.Conclusions Guselkumab every 8 weeks led to consistent improvements through week 24 in joint, skin, PRO and composite outcomes versus placebo across diverse baseline-defined subgroups of TNFi-IR patients with PsA. Response rates increased or were durable through week 48 within most subgroups.